Cidade média de limiar superior: um estudo a partir de Ribeirão Preto (SP) - Sant'Anna, Letícia Moreira [UNESP] (2015)
This papper aims to discuss Ribeirão Preto as a switched-over intermediate city classification, contrastating with the concept of Metropolitan Region of Ribeirão Preto. The agribusiness sector will be analysed as the main responsible for the representation of Ribeirão Preto city as an Agribusiness Center. Due to this fact, Sertãozinho city example will be presented as Agribusiness City, where acctually concentrates the agro-industrial complex of sugarcane production, while Ribeirão Preto is in fact centralizes management activities. According to the balance of trade analysis, other elements showed up and fortifies the role of this cities. These elements unfolded the analysis of higher education guideline and shopping malls. We also analyzed the urban network of Ribeirão Preto under the concept of the Região de Influência das Cidades (REGIC) and the creation of the project Metropolitan Region of Ribeirão Preto in order to strengthen the central hypothesis as a switched-over medium sized city. In order to reach this point, besides the analysis of the data we had t literature review of the Medium Sized Cities and Urban Network concepts and Spatial Interactions and Switched- over terms